Modelling of airflow circulation systems in wood drying processes. (16th May 2011) - Liu, Yaqiu; Chang, Liang; Zhu, Liangkuan
The quality and uniformity of the wood drying are determined greatly by the airflow distribution, airflow velocity, pressure, temperature, humidity in the drying kiln and these factors are significant to the fluidics research on wood drying wind circulation systems. In this paper, an airflow-coupling model and a stack centre model for wood drying wind circulation systems are studied by using renormalisation group k-ε turbulence model and wall-function method, the unified modelling theory is used to predict the changing of airflow section distribution, airflow velocity, pressure and temperature in the columned structure. In addition, the emulation researches on the airflow-coupling model and wind-resistance model which is built based on the wind-resistance experiments are done by using fluid tool. Experimental results show that the proposed modelling approach for wood drying wind circulation is feasible and effective.